PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN TEKNIK DASAR SHOOTING FUTSAL (Studi kasus SMAN 3 Karawang) - Himawan, Firman (Jurnal Ilmiah Mandala Education (JIME), 2022)
In the futsal game shooting technique is the most important technique in the futsal game, this is because goals are created from shooting abilities, the more you enter the ball into the opponent's goal, the greater the chance to win the game. Every player is required to have good shooting technique skills. There are two kinds of kicks, namely passing and shooting, both kick techniques must be mastered correctly by futsal athletes, because if the athletes can master these techniques correctly, they will definitely be able to develop their skills in processing the ball, which will certainly deliver them. become a professional player. The purpose of this study was to determine the effect of using audio-visual media on basic shooting technique skills in SMAN 3 futsal extracurricular activities. This study uses a research design of One Group Pretest-Posttest Design, with a futsal extracurricular student population of 20 students. The sample used in this study was 20 students, the research data analysis was carried out by comparing the pretest and posttest data after treatment using one sample t-test. The results showed that the average pretest was 1.322, with the highest score of 11 and the lowest score of 6. Meanwhile, during the post test, the average score was 1,593. With the highest score of 15 and the lowest score of 10. Thus it can be seen that there is an increase in the results of the basic futsal shooting technique skills from the pretest and posttest. This proves that the use of audio-visual media is effective in improving the basic skills of shooting futsal techniques.